Research on Opportunities, Challenges, and Countermeasures for the Development of the Cruise Ship Interior Outfitting Technology Major in China - Rui, Jiang (Journal of Social Science and Humanities, 2025)
With the continuous eastward shift of the global cruise industry and the launch of China’s domestic cruise shipbuilding market, the talent gap in cruise ship interior outfitting technology, as a key supporting technology, is becoming increasingly prominent. This paper aims to explore the historical opportunities and practical challenges faced by Chinese universities in establishing the Cruise Ship Interior Outfitting Technology major and proposes corresponding development strategies. The study argues that national policy support for high-end shipbuilding, substantive breakthroughs in domestic cruise shipbuilding projects, the industrial chain demand driven by a huge consumer market, and the gradual deepening of international cooperation collectively constitute significant opportunities for developing this major. However, the program development also faces multiple challenges, including the lack of a mature curriculum system and textbooks, a severe shortage of “dual-qualified” faculty, high investment costs and difficulties in constructing training facilities, and the challenge of aligning with international industry standards. To address these challenges, this paper proposes establishing a collaborative education model involving government, industry, enterprises, and schools; developing modular and project-based curriculum systems; creating high-level “dual-qualified” teaching teams through multiple pathways; and jointly building and sharing high-level training bases. Through these countermeasures, it is expected to systematically advance the development of the Cruise Ship Interior Outfitting Technology major, providing intellectual and talent support to fill the domestic talent gap in related fields and bolster the development of the national cruise industry.